Web archive metadata elements for Selangor royal web archive content collections / Noraizan Amran ... [et al.] - Amran, Noraizan; Saiful Bahry, Farrah Diana; Mohamed Shuhidan, Shamila; Husaini, Haslinda (Faculty of Information Management, 2023)
Describing web archive metadata in implementing web preservation is essential in the overwhelming digital born documents' generation. The primary purpose of metadata generation in this study is to encourage preservation initiative specifically for Selangor royal web collections. The Design Science Research (DSR) stages implemented in this study are significant indication that display the tasks involved made it possible for the web archiving implementation and metadata creation. A total of sixteen Selangor royal web archive metadata elements were created and identified after validating and mapping with existing metadata standards. Those metadata elements are functional in the implementation of object structure of web preservation repository. This study is indispensable to contribute quality of content retrieval and cultivating a good practice on web archiving initiatives both in social and practical context.